2019 International Conference on Electrical, Computer and Communication Engineering (ECCE) 2019
DOI: 10.1109/ecace.2019.8679365
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Machine Learning Techniques to Predict Diabetes Mellitus

Abstract: Diabetes mellitus is a common disease of human body caused by a group of metabolic disorders where the sugar levels over a prolonged period is very high. It affects different organs of the human body which thus harm a large number of the body's system, in particular the blood veins and nerves.Early prediction in such disease can be controlled and save human life. To achieve the goal, this research work mainly explores various risk factors related to this disease using machine learning techniques. Machine learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(34 citation statements)
references
References 10 publications
0
33
0
1
Order By: Relevance
“…When it comes to utilising machine learning methods to predict diabetes or other diseases, different models have been proposed in recent years. The paper [12] used four separate machine learning algorithms to predict Diabetic Mellitus among the adult population, and the decision tree was found to provide higher accuracy. In [13], different decision tree classifiers are applied and evaluated based on their true positive rate and precision.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to utilising machine learning methods to predict diabetes or other diseases, different models have been proposed in recent years. The paper [12] used four separate machine learning algorithms to predict Diabetic Mellitus among the adult population, and the decision tree was found to provide higher accuracy. In [13], different decision tree classifiers are applied and evaluated based on their true positive rate and precision.…”
Section: Introductionmentioning
confidence: 99%
“…Faruque [15] and Kandhasamy [16] found that the prediction effect of C4.5 decision tree model was signi cantly higher than that of SVM model. The results of this study showed that the prediction effects of SVM and CART models were similar, and the difference in AUC value was not statistically signi cant, and the prediction effects of the two models were slightly better than that of C4.5 decision tree model.…”
Section: Discussionmentioning
confidence: 99%
“…Today, diabetes has become one of the most important and recognized diseases in the world, not only because of its terrible effects on the human body, but also because of its difficult previous diagnosis, according to medical data it is estimated that this disease will increase from 376 billion to 490 billion in 2030 [1], in another aspect, diabetes presents some symptoms, such as continuous urination, increased thirst, expanded craving and weight reduction [2]. Diabetes can be divided into several categories among the main ones are type 1, it is caused due to total insufficiency of insulin secretion and type 2 is caused due to the combination of immunity to insulin action and insulin deficiency [3].…”
Section: Introductionmentioning
confidence: 99%